Enhancing learners' mathematics achievement by using a gamified flipped classroom instructional strategy - Sulaimon, Jamiu Temitope; Manditereza, Blandina; Chamboko-Mpotaringa, Mavis (Jurnal Gantang, 2025)
Flipped learning is an educational approach that inverts the traditional teaching pattern by giving pupils access to learning materials before class, while using classroom time to deepen their understanding. However, few studies investigate whether low-basic learners possess the readiness and digital literacy to benefit from this approach. Hence, this study examined the impact of implementing a Gamified Flipped Classroom Instructional Strategy on enhancing mathematics achievement among lower primary learners in Ilorin West Local Government Area of Kwara State, Nigeria. Employing the pre and posttest control group in line with a quasi-experimental design, 74 learners from two private primary schools participated in the research. This study employed three validated research instruments: the Mathematics Achievement Test (MAT), the Guide for Gamified Flipped Classroom Instructional Strategy (GGFCIS), and the Guide for Control Group (GCG). The MAT instrument demonstrated a reliability coefficient of 0.74 using the test-retest method. Two hypotheses were evaluated by using Analysis of Covariance (ANCOVA) at a 0.05 significance level. Results indicated a significant positive effect of the gamified flipped classroom instructional strategy on learners' academic achievement in mathematics. However, no significant interaction between treatment and gender was found. The study concluded that regardless of gender, the instructional strategy improved the academic achievement of lower basic learners in mathematics. The study recommended that primary school teachers undergo training in using the gamified flipped classroom instructional Strategy for teaching mathematics to lower basic primary learners, as it promotes academic success while encouraging parental involvement in learners' learning.